Globalizzazione: e la popolazione? Le relazioni fra demografia e mondo globalizzato - SALVINI, Maria Silvana (Studi e saggi, 2021)
Globalization is a huge topic and here we have chosen to describe only a few pieces of a complex mosaic. Its description has a historical perspective and ranges from economic to medical, from social to demographic issues. It aims to reconstruct a background picture that places demographics in the scenario of international relations. It is possible to distinguish some themes: 1. The population is aging and enriching itself. Convergence often collides with delayed demographic transition. 2. The economic weight and political power are shifting towards Asia. 3. The technological revolution affects almost all aspects of society. 4. The increase in energy consumption and new production models make it difficult to manage the scarcity of resources. 5. Interdependence between countries does not go hand in hand with strengthening global governance.